(untitled) (Advances in Applied Biological Research, 2025)
Thalassemia Major, a severe genetic blood disorder, necessitates frequent blood transfusions to manage low hemoglobin levels. This case highlights the recovery journey of Dibyanshu Pani, a 4-year-old boy from Odisha, diagnosed with Blood Transfusion Dependent Thalassemia Major in April 2023. Initially treated at SCB Medical College, Cuttack, and subsequently in Mumbai, Dibyanshu underwent frequent transfusions every 20 days to maintain his hemoglobin levels, which fluctuated between 5 and 9. In July 2023, his family opted for an alternative approach under Dr. Namita’s guidance, incorporating integrative therapies such as the DIP Diet, Living Water Therapy, Sunlight Exposure, and HWI Therapy. Remarkably, Dibyanshu’s condition stabilized, reducing his dependence on transfusions. By October 2023, his hemoglobin levels were maintained between 6.8 and 7.5 without regular transfusions. His family’s adherence to integrative therapies transformed his prognosis, with the frequency of transfusions decreasing to once every eight months. In August 2024, a sudden episode of diarrhea necessitated a single transfusion. Today, Dibyanshu leads a healthy life, free from medications, following a holistic lifestyle. This case underscores the potential of integrative therapies in managing chronic conditions like Thalassemia Major, reducing medical dependence, and improving quality of life.